e Baptist Church in Haarlem (Bulletin KNOB, 1999)
The classicist Baptist Church in Haarlem has almost completely escaped historiography of Dutch architecture, although its building history is very well documented. The first plans for the church date from 1672, after the joining together of two groups of Baptists. A plot between Grote Houtstraat, Peuzelaarsteeg, Frankestraat and Anegang was reserved as the building site.On December 26, 1674 the first design was completed, but for financial reasons the construction was postponed until 1682. Eventually it took place between May 1682 and March 1683. The building plans are illustrated with a series of thirteen design drawings. The earliest design, probably dating from 1674, shows a traditional, three-bay and axial clandestine church with galleries (ill. 2). The subsequent designs have a more modern, more centralizing character, in a 3 : 4 proportion (ill. 3, 4 and 5). This proportion corresponds to the proportions of the existing church, measured across the central lines of the walls. In three later designs, having a groundplan proportion of 4 : 5, this striving for centralization is worked out in greater detail (ill. 8, 9 and 10).The remaining five drawings concern the furnishing of the church and therefore probably date from the last phase of the design process (1681-1683): variations on pulpits, a plan for church pews with pulpit and baptismal garden, and a ground plan with four different positions of the pulpit (ill. l 1-15). The fact that one of the designs was signed by the Haarlem painter Jan de Bray (ill. 12) suggests the latter's involvement in the design and furnishing of the church building.An argument in favour of attributing the church to De Bray could be that since 1677 he is regularly mentioned as architect ('constmeester', 'constwerker', 'boumeester'). Moreover, the use of the Haarlem foot measure in the church building indicates a Haarlem architect. Finally, there is evidence that De Bray had contacts with a prominent Baptist citizen in Haarlem. Although there is no architectural work by him that we know of, so that comparison is not possible, the classicist De Bray is a serious candidate as the designer of the Baptist Church in Haarlem.